Rethinking Sovereign Debt - Odette Lienau (Harvard University Press, 2014)
Sovereign debt markets have demonstrated incredible resilience despite a century of dramatic political and economic upheaval. Among the most remarkable aspects of the contemporary debt regime is the degree to which expectations of borrowers remain relatively uniform even in the face of such major shifts. These basic expectations resolve into one background rule: sovereign borrowers must repay, regardless of the circumstances of the initial debt contract, the actual use of loan proceeds, or the exigencies of any potential default. This is not to say that countries always pay; certainly, they do not. But the background rule remains, and it sets the standard by which creditors and others form their reputational judgments and against which sovereign borrowers are evaluated and chastised. This repayment norm helps to immunize the debt regime from serious challenge and to stabilize the massive sums at stake. In particular, it buttresses our avoidance of prickly questions about fairness and appropriateness in the international economic arena. Several troubling queries in recent decades include: Should a black-African-led South Africa really be expected to repay apartheid era debt? Or, given that Saddam Hussein was a dictator who used funds for the oppression of a majority of Iraqâ€™s population, would it be appropriate to require future Iraqi generations to pay for his iniquity? More generally, who counts as the â€œsovereignâ€ in these debt situationsâ€”is sovereignty just the legal shell for whoever happens to control a territory, or does it imply underlying principles of legitimate representation or public benefi t? And how might all this fi t into assessments of a countryâ€™s creditworthiness? Notwithstanding such questions, the repayment norm exerts a particular kind of power in international economic relations by shaping expectations of appropriate action in the area of sovereign debt. The rule is strengthened by its popular identity as a market principle, with effects that can be identifi ed and measured but that ultimately cannot be changed. A study commissioned by the United Nations Conference on Trade and Development (UNCTAD)